Long‐term outcomes of implants placed after vertical alveolar ridge augmentation in partially edentulous patients: a 10‐year prospective clinical study. Issue 10 (1st August 2016) - Roccuzzo, Mario; Savoini, Matteo; Dalmasso, Paola; Ramieri, Guglielmo
Abstract: Aim: The aim of this study was to evaluate the long‐term clinical results around non‐submerged implants placed after vertical alveolar ridge augmentation. Material and methods: The original population consisted of two groups of partially edentulous patients (Clinical Oral Implants Research, 15, 2004, 73; Clinical Oral Implants Research, 18, 2007, 286), receiving a total of 82 implants, after a vertical bone augmentation of at least 4 mm. Following cementation of the fixed dental prostheses, patients were asked to follow an individualized supportive periodontal therapy (SPT) program for an appropriate clinical and radiographic follow‐up. Results: At the 10‐year examination, seven of the 41 patients were lost to follow‐up. During SPT, additional antibiotic and/or surgical therapy was necessary in 18 implants, and four of these implants were removed for biological complications. The overall implant survival rate was 94.1%. The mean interproximal bone loss (BL) was 0.58 ± 0.57 mm. Conclusions: The results of this study confirmed that implants, placed after vertical augmentation and followed by an adequate SPT, offer predictable long‐term results. Nevertheless, patients whose bone atrophy was consequence of a previous history of periodontitis presented a statistically significant greater BL.